Experimental analysis of glass failure criteria under different thermal conditions - Mishra, Raj Kumar; Sharma, Pawan Kumar; Kumar, Ravi (Frontiers in Thermal Engineering, 2024)
The initiation of the first crack mainly determines the criteria for glass failure. However, the extended consequences of cracking, with the formation of multiple cracks merging, result in fallout conditions under varying thermal loads that become more critical. Point-supported glass arrangements are globally used in high-rise and energy-efficient buildings for architectural ingenuity aimed at a low budget. However, the formation of cracks due to thermal load resulting in glass breakage could infuriate the overall fire dynamics of the enclosed area.Therefore, experimental study and prediction of glass failure become very crucial. The present experimental study focuses on finding the most critical parameter that may quantify the cause of glass failure and further breakage in fallout conditions under varying thermal loads. 45 experiments were carried out on float glass of 300×300 mm 2 with 4 mm, 6 mm, 8 mm, 10 mm, and 12 mm with continuous fuel supply arrangements. Critical parameters analysed were the time of crack initiation, glass temperature at the time of cracking, maximum temperature difference at glass failure, and thermal strain caused by the temperature difference on the glass surface. The range of minimum and maximum temperature difference recorded on the glass surface for the present study was between 30 -35 ℃ and 55 -60 ℃ at the breakage time for all the experiments. The Maximum temperature difference measured was 56.99 ℃ on the 12 mm glass surface, and the corresponding maximum thermal strain found was 482 × 10 -6 mm/mm. The maximum heat release rate was found to be approximately 200 kW. Maximum heat flux was found in the range of 10.33 kW/m 2 to 21.14 kW/m 2 . A correlation was also developed using the least square method for all the thicknesses, which is well correlated with the glass thickness per unit length.